Preliminary report on the project for an Etymological dictionary of the Angas-Sura group of Chadic languages - Takács, Gábor (Lingua Posnaniensis, 2024)
The brief report announces the current work on the forthcoming first two fascicles of an etymological dictionary elaborating the Afro-Asiatic background of a Chadic language group, one of the first ones in this genre in the history of Chadic linguistics.